Utilization of Artificial Intelligence (AI) in The Employee Recruitment Process: A Qualitative Study on Multinational Companies in Indonesia - Zaskia Ardhani (Jurnal Impresi Indonesia, 2025)
This study aims to explore the perceptions and experiences of Human Resources (HR) practitioners regarding the use of Artificial Intelligence (AI) in the recruitment process at multinational companies in Indonesia. Using an exploratory qualitative approach, data were collected through in-depth interviews, observations, and document analysis involving eight informants from five different companies. The findings indicate that AI has a positive impact on improving efficiency and accuracy during the early stages of recruitment, such as application screening and psychometric analysis. However, several challenges arise concerning system transparency, potential algorithmic bias, and candidates' perceptions of unfairness. This study also emphasizes the importance of the human role in the final stages of recruitment, particularly in decision-making processes that require empathy, intuition, and ethical considerations. Thus, collaboration between AI and HR is considered the most ideal approach to create a recruitment process that is efficient, fair, and human-centered.